Designing an information system to automate service management at the enterprise - Orlov Vasiliy; Kukartsev Vladislav; Suprun Elena; Gek Danil; Ageev Daniel (E3S Web of Conferences, 2023)
In this paper we consider the development of an automated information system for a coffee shop that meets the current standards and needs of this business. Emphasis is placed on both hardware infrastructure and content structure. This AIS system provides all the necessary functionality for a coffee shop to successfully run its business, including convenient menu search, online ordering and payment. In addition, the application helps to reduce the workload of the staff, as many tasks that were previously performed by employees can now be automated and performed by the system being developed.